Pendidikan Agama Berbasis Multietnik di SMAN 9 Bandar Lampung - Riyu zen (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
Life Skills education can be obtained by students from the relevant educational unit and from other formal and nonformal education units. For personal skills, students are directed to be able to live in a society well, independent, and responsible for the task that has been taken by the side. For social skills, an education related to social skills is integrated in Civics and Sociology lessons. Another activity that is the education of social skills, namely by training children to care for each other by providing assistance every time there is a natural disaster nationally and regionally. As for the academic skills and integrated vocational skills in science subjects, Mathematics, Language, Penjaskes, and art. This attitude is given intensively through the giving of material that is both theoretical and the paraktis. With this skill students are expected to have sufficient knowledge in living their lives. This will be reflected in the worldview and the scientific insights that are implemented in everyday life.